The urgency of learning social studies (IPS) in forming pluraris character and increasing the existence of Indonesian culture in elementary schools - Lestari , Nyoman Ayu Putri; Wahyuni, Luh Tu Selpi; Lasmawan , I Wayan; Kertih, I Wayan (Universitas Nusantara PGRI Kediri, 2023)
This study aimed to examine the urgency of Social Studies (IPS) learning in forming pluralist characters and increasing the existence of Indonesian culture in elementary schools. The method used is a literature review, by collecting and analyzing relevant sources related to the role of Social Studies in character building and cultural preservation. Important findings from this study indicated that social studies learning has a vital role in providing an understanding of Indonesia's cultural diversity, encouraging tolerance, respecting cultural differences, and increasing student awareness of the importance of maintaining the existence of Indonesian culture. Thus, Social Studies learning in elementary schools is an effective means of forming the pluralist character of students and strengthening the existence of Indonesian culture. The results of this research are expected to provide a deeper understanding of the urgency of Social Studies (IPS) learning in facing the challenges of globalization and strengthening the cultural identity of Indonesia among elementary school students.